Biorenewable resources : engineering new products from agriculture - Brown, Robert C. (John Wiley & Sons Inc., 2014)
Biorenewable resources are the dedicated energy crops, agricultural residues, and organic wastes that serve as feedstocks in the production of fuels, chemicals, energy, and materials for the emerging bioeconomy. This edition provides an overview of the field that incorporates significant advances made in the field over the last decade. It is thoroughly revised and expanded to better serve the needs of students, professionals, and researchers working on the production and processing of biorenewable resources. Chapters provide grounding in fundamental concepts of engineering thermodynamics and organic chemistry relevant to the field, as well as provide practical guidance in feedstock production, processing, economics, and policy. --